Avaliação do efeito do cobalto ou zinco na estabilidade do composto Ti6Si2B em ligas produzidas por moagem de alta energia e subsequente sinterização a plasma - Ferreira, Nelson Damásio (2017)
Ti-Si-B alloys containing Ti6Si2B present potential for high-temperature structural applications due to their physical and chemical properties such as low thermal expansion coefficients and good oxidation resistance. The present work aims to investigate on effect of cobalt or zinc addition (varying its amount in 2 at.-% and 6 at.-%) on the stability of the Ti6Si2B compound in (66,7-x)Ti-xCo-22,2Si-11,1B and (66,7-x)Ti-xZn-22,2Si-11,1B alloys (at.-%) produced by high-energy ball milling and subsequent spark plasma sintering (1100oC, 12 min, 20 MPa). Alloy powders were produced in a planetary Fritsch P-5 ball mill using WC-6Co vial (225 mL) and balls (10 mm de diameter), rotary speed of 300 rpm and a ball-to-powder weight ratio of 10:1. Samples were collected after different milling times: 20, 60, 180, 300 min. Cylinder bodies with 10 mm diameter were consolidated by spark plasma sintering under controlled atmosphere. As-milled powders and sintered samples of Ti-Co-Si-B and Ti-Zn-Si-B were characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM) and dispersive energy spectrometry (EDS) techniques. The increased milling time has contributed to enhance the chemical and microstructural homogeneities of the Ti-xCo-22Si-11B and Ti-xZn-22Si-11B (x = 2 and 6 at.-%) powder mixtures, which it was accomplished by formation of supersaturated Ti solid solutions. A amount of Ti6Si2B was reduced in microstructures of the sintered Ti-Co-Si-B and Ti-Zn-Si-B alloys increasing the cobalt or zinc amounts in nominal composition of these alloys, limiting these elements in multicomponent alloys based on Ti+Ti6Si2B system for development structural materials. Belong the TiB and Ti5Si3 phases other cobalt-rich or zinc-rich unknown phases were also found in microstructures of the spark plasma sintered Ti-Co-Si-B and Ti-Zn-Si-B alloys, respectively. Despite the adopted parameters, 1100oC/12 min/20MPa, the spark plasma sintering produced the dense Ti-xCo-22Si-11B and Ti-xZn-22Si-11B (x = 2 and 6 at.-%) alloys. In this step, the longer milling times have contributed for occurrence of atomic diffusion mechanisms needed to obtain the equilibrium microstructure.